(untitled) (Medico Legal Update, 2021)
The aims of this study are to determine the virulence factors of parasitic infestation, especially of the E. histolytic parasite, for persons with cancer and parasites. This study contain 2 groups: Group (G1) People with cancer and diarrhea due to the parasite (50)and (G2) People with diarrhea and parasites (24), Stool samples were collected from both groups for the purpose of confirming the diagnosis of the microscopically diagnosed parasite,Molecular testing is used to confirm the diagnosis of the parasite first and then determine or diagnose its virulence factors, The result of the diagnosis of the parasite is (89.189%) in the study groups as a result of the PCR examination and the result of the diagnosis of the parasite’s virulence factor is 100.0%. The study concluded that all parasitic infestations had virulence factors cysteine protease (CP)